(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article deals with significant information about Spanish language: its role in modern life and benefits of learning Spanish as a foreign language. On the other hand, effective strategies and methods for teaching and learning Spanish were discussed in the article.